Improved anti-amnesic activity of tacrine loaded pla polymeric nanoparticles - FELIX JOE .V,; SATHESH KUMAR. S, (International Journal of Pharma and Bio Sciences, 2017)
Tacrine (9-amino-1,2,3,4-tetrahydroacridine monohydrochloride) a reversible cholinesterase inhibitor, for the treatment of mild to moderate Alzheimer disease. The objective of this study was to formulate and characterize tacrine loaded poly (lactic acid) (PLA) nanoparticles (TPLN) for improving the therapeutic activity and to reduce adverse drug reactions by targeting to brain. TPLN with varying polymer ratios were prepared by nanoprecipitation method and subjected to various physico-chemical evaluations like determination of drug content, particle size, zeta potential, entrapment efficiency and in vitro release of tacrine from the polymeric nanoparticles.The particle size of various trials ranged from 219nm to 251nm. The PLA nanoparticles were able to entrap tacrine up to 74.53±1.3%. The release of tacrine from TPLN-3 at the end of 24hrs was found to be 92.59%. The in vitro cytotoxicity of the TPLN indicates that the IC50 of the tacrine shown an improvement in the reduction of the IC50, whereas, plain nanoparticles had not shown any severe cytotoxicity. In cellular uptake studies, the optimized formulation TPLN-3, showed increased intracellular accumulation when compared with pure drug and the control. The results further suggest the increase in extent of transport of tacrine in TPLN treated mice with a remarkable improvement of the therapeutic efficacy.